2017
DOI: 10.1080/02640414.2017.1405709
|View full text |Cite
|
Sign up to set email alerts
|

Reallocating sitting time to standing or stepping through isotemporal analysis: associations with markers of chronic low-grade inflammation

Abstract: Although high levels of sitting time are adversely related to health, it is unclear whether moving from sitting to standing provides a sufficient stimulus to elicit benefits upon markers of chronic low-grade inflammation in a population at high risk of type 2 diabetes (T2DM). Three hundred and seventy two participants (age = 66.8 ± 7.5years; body mass index (BMI) = 31.7 ± 5.5kg/m; Male = 61%) were included. Sitting, standing and stepping was determined using the activPAL3 device. Linear regression modelling em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 51 publications
6
29
0
Order By: Relevance
“…These results are broadly similar to previous evidence from compositional data analyses [ 23 , 25 , 37 , 38 , 39 , 40 ], as well as previous isotemporal substitutional analyses using traditional methodologies [ 13 , 14 , 15 , 16 , 17 ]. As with previous evidence, movement appears to be the most influential physical behaviour.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…These results are broadly similar to previous evidence from compositional data analyses [ 23 , 25 , 37 , 38 , 39 , 40 ], as well as previous isotemporal substitutional analyses using traditional methodologies [ 13 , 14 , 15 , 16 , 17 ]. As with previous evidence, movement appears to be the most influential physical behaviour.…”
Section: Discussionsupporting
confidence: 90%
“…Physical activity has been shown to reduce morbidity and mortality [ 10 , 11 , 12 ]. Research has examined reallocating one behaviour to another, showing positive results for increasing movement (stepping, LIPA, and MVPA) by decreasing sedentary time [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. With the growing interest in sedentary behaviour, there has been an increase in the use of thigh-worn accelerometers that can measure the postures of sitting and standing, rather than infer sitting time through lack of movement, which has been done with waist-worn accelerometers [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent experimental evidence has demonstrated a reduction in glucose, insulin and blood pressure following regular standing and walking breaks (i.e., every 20–30 min), with total reductions in sitting varying from 28 min to 60 min across the course of a day [ 12 , 13 , 15 , 16 , 18 ]. Furthermore, using statistical modelling we have observed that interchanging 30 mins/day of sitting (measured with the activPAL) with standing and stepping is associated with favourable differences in insulin sensitivity [ 9 ] and inflammation [ 10 ]. In a similar analysis, interchanging 2 h of sitting/day with standing or stepping was associated with favourable differences in glucose, triglycerides, cholesterol and waist circumference [ 11 ].…”
Section: Methodsmentioning
confidence: 99%